PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAPKINERJAKARYAWANPADAINDUSTRI HOME VANILLA - Muji Harjanti, 13.05.51.0119 (Students Journal of Economic and Management, 2017)
This study aims to determine and analyze the effects of compensation, motivation and work discipline on employee performance.The sample of research is 70 employees in Home Industry Vanilla. In this research using census sampling technique that is taking all population as research sample. Technique analysis of the data used include the test validity, reliability testing with Alpha Cronbrach, multiple regression analysis, T test to test and approve the research hypothesis.The test results obtained that there is a positive and significant effect of compensation on employee performance, there is a positive and significant effect of motivation on employee performance, There is a positive influence and significant work discipline on employee performance.Â  Keywords: compensation, motivation, work discipline and employee performance